Survey on the Presence of Bacterial and Parasitic Zoonotic Agents in the Feces of Wild Birds - Valentina Virginia Ebani; Lisa Guardone; Fabrizio Bertelloni; Stefania Perrucci; Alessandro Poli; Francesca Mancianti (Veterinary Sciences, 2021)
Wild avifauna may act as fecal source of bacterial and parasitic pathogens for other birds and mammals. Most of these pathogens have a relevant impact on human and livestock health which may cause severe disease and economic loss. In the present study, the fecal samples collected from 121 wild birds belonging to 15 species of the genera Anas, Tadorna, Fulica, Arddea, Larus, Falco, Athene, Accipiter, and Columba were submitted to bacteriological and molecular analyses to detect Brucella spp., Coxiella burnetii, Mycobacterium spp., Salmonella spp., Cryptosporidium spp., Giardia spp., and microsporidia. Four (3.3%) animals were positive for one pathogen: one Anas penelope for C. burnetii, one Larus michahellis for S. enterica serovar Coeln, and two Columba livia for Encephalitozoon hellem. Although the prevalence rates found in the present survey were quite low, the obtained results confirm that wild birds would be the a potential fecal source of bacterial and parasitic zoonotic pathogens which sometimes can also represent a severe threat for farm animals.